2019
DOI: 10.1101/721449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome association studies of neuropsychiatric traits in African Americans implicatePRMT7in schizophrenia

Abstract: 14In the past fifteen years, genome-wide association studies (GWAS) have provided novel insight into the genetic architecture of various complex traits; however, this insight has been primarily focused on populations of European descent. This emphasis on European populations has led to individuals of recent African descent being grossly underrepresented in the study of genetics. With African Americans making up less than two percent of participants in neuropsychiatric GWAS, this discrepancy is magnified in dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Many genetic studies have demonstrated population-specific characteristics due to differences in underlying genetic architecture and environmental exposures, highlighting the importance of investigating trait/disease heterogeneity in population genetic studies. There have been GWAS studies reported in Indian (Periyasamy et al, 2019), African American (Fiorica & Wheeler, 2019) and Latin American (Bigdeli et al, 2019) populations but, to date, large scale schizophrenia GWAS has primarily been investigated in people of European ancestry and more recently East Asian ancestries. The largest schizophrenia GWAS in individuals of East Asian ancestries reported 21 independent associations in 19 loci, which included the top three associations shared with the European studies, and an additional 14 associations compared to the previous study of Chinese ancestry (Lam et al, 2019).…”
Section: Common Genetic Variationmentioning
confidence: 99%
“…Many genetic studies have demonstrated population-specific characteristics due to differences in underlying genetic architecture and environmental exposures, highlighting the importance of investigating trait/disease heterogeneity in population genetic studies. There have been GWAS studies reported in Indian (Periyasamy et al, 2019), African American (Fiorica & Wheeler, 2019) and Latin American (Bigdeli et al, 2019) populations but, to date, large scale schizophrenia GWAS has primarily been investigated in people of European ancestry and more recently East Asian ancestries. The largest schizophrenia GWAS in individuals of East Asian ancestries reported 21 independent associations in 19 loci, which included the top three associations shared with the European studies, and an additional 14 associations compared to the previous study of Chinese ancestry (Lam et al, 2019).…”
Section: Common Genetic Variationmentioning
confidence: 99%
“…Genome-wide association studies and PrediXcan (a genebased association method) for schizophrenia and bipolar disorder identified that PRMT7 was significantly correlated with schizophrenia. Further analysis showed that PRMT7 was highly expressed in the CA1 field of the hippocampus, and PRMT7 -/mice displayed defects in social behaviors [78]. Recent studies further revealed that PRMT7 -/-CA1 neurons exhibited HCN (hyperpolarization-activated, cyclic-nucleotide-gated) channel current dysfunction, which might be attributed to the decreased HCN protein levels mediated by SHANK3 downregulation [68,79].…”
Section: Prmt7 In Neuronal Developmentmentioning
confidence: 99%